Frequency of adverse reactions after subcutaneous allergen immunotherapy in children - Senay Sasihuseyinoglu, Ayse; Doğruel, Dilek; Ufuk Altıntaş, Derya (ENT Updates, 2020)
Objective: Subcutaneous allergen immunotherapy (SCIT) is an effective treatment method for allergic rhinitis, asthma and venom allergy. The aim of this study was to evaluate the frequency of adverse reactions in children undergoing SCIT. Methods: This retrospective study included patients that underwent SCIT in our clinic for a period of five years due to a diagnosis of Apis mellifera venom allergy or allergic asthma and/or rhinitis. 303 patients were divided into groups based on the form of SCIT administered and the presence of injection-related reactions. Results: Mean age at the initiation of SCIT was 10 (range, 5-18) years old. SCIT for aeroallergens was administered to 289 (95.4%) patients and SCIT for venom to 14 (4.6%) patients. Local reactions were observed in 54 (17.8%) and systemic reactions developed in 4 (1.3%) patients. The local reactions mostly occurred after SCIT with Apis mellifera venom (100%), followed by house dust mite (20.6%), mold (16.7%) and grass pollen (16.7%). Conclusion: Although SCIT is a safe treatment method used for allergic diseases, it must be administered only in centers with appropriate emergency equipment due to the risk of side effects.